An Analysis of Nearly One Billion Dollars of Aquaculture Grants Made by the US Federal Government from 1990 to 2015. Issue 5 (7th May 2017) - Love, David C.; Gorski, Irena; Fry, Jillian P.
Abstract: The aquaculture industry relies on federal investments to stimulate aquaculture research and development (R&D). We conducted this study to track federal spending for aquaculture using a large database of 2957 US federal research grants awarded from 1990 to 2015. During that period, 1.04 billion US dollars (USD) were spent on aquaculture research, with 919 million USD from federal agencies and 123 million USD in matching funds. By comparison, over the same time frame, the US Department of Agriculture's R&D spending was 41 billion USD. Federal grant funding for aquaculture had a 37‐fold return on investment since 2000. Microalgae, oysters, salmon and trout, catfish, and shrimp received the most grant support, and the most common topics/disciplines were aquaculture production sciences, aquatic animal health and disease, genetics and breeding, and nutrition. Our findings can be used to identify research gaps and inform federal policy, grant making, and budget allocation.